Benefits of Using Short Stories - Akar, Sıla Selver; Zabitgil Gülseren, Özlem; Gülseren, Özlem Zabitgil (İstanbul Sabahattin Zaim Üniversitesi, 2020)
This article examines if digital stories affect word acquisition of English language learners at the English preparatory school level. To realize this aim, preparatory school students at the Yeni Yüzyıl University with A2 language proficiency were included in an experimental study. This study came about as a result of our curiosity of the impact of digital reading practices on the vocabulary learning of students, because word knowledge impacts overall language development considerably. A pre and post-test design was used to inquire how digital stories affect the vocabulary acquisition of English Language learners. Digital stories are read from the screen with the practice of various comprehension and discussion activities. Students could also reach these stories outside of the classroom if they choose to read and practice more. This research aims to gather information about the use of digital stories in language classes and its impact on vocabulary learning. We would like to compare the results of the traditional reading group with the experimental group who will receive digital story reading application in addition to the traditional story reading from their course book. This knowledge will contribute to the literature of vocabulary learning in English language teaching. Also, the results can initiate various technology based inquiries as it relates to the L2 vocabulary development and reading performance. Depending on the results of this study we will be able to inquire further studies including different age groups and different language learning contexts with creative Information and Communication Technology (ICT) reading applications.
İZÜ Sosyal Bilimler Lisansüstü Öğrenci Kongresi, 6-7 Haziran 2020 (ONLINE)
Keywords: Vocabulary Learning; Digital short story; Second Language Learning